On the onset of deformation twinning in the CrFeMnCoNi high-entropy alloy using a novel tensile specimen geometry. (July 2019) - Thurston, Keli V.S.; Hohenwarter, Anton; Laplanche, Guillaume; George, Easo P.; Gludovatz, Bernd; Ritchie, Robert O.
Abstract: Deformation-induced nanoscale twinning is one of the mechanisms responsible for the excellent combination of strength and fracture toughness of the single-phase, face-centered cubic CrMnFeCoNi (Cantor) alloy, especially at cryogenic temperatures. Here, we use a novel, modified dogbone geometry that permits the sampling of varying stress and strain regions within a single tensile specimen to characterize the onset of twinning in CrMnFeCoNi at 293 K, 198 K and 77 K. Electron backscatter diffraction (EBSD) and backscattered electron (BSE) imaging revealed the presence of deformation nano-twins in regions of the samples that had experienced plastic strains of ∼25% at 293 K, ∼16% at 198 K, and ∼8% at 77 K, which are similar to the threshold strains described by Laplanche et al. ( Acta Mater. 118, 2016, 152–163). From these strains we estimate that the critical tensile stress for the onset of twinning in this alloy is on the order of 750 MPa. Graphical abstract: Image 1